2002
DOI: 10.1074/jbc.m200356200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanics of Cardiac Titin's PEVK and N2B Spring Elements

Abstract: Titin is a giant elastic protein that is responsible for the majority of passive force generated by the myocardium. Titin's force is derived from its extensible I-band region, which, in the cardiac isoform, comprises three main extensible elements: tandem Ig segments, the PEVK domain, and the N2B unique sequence (N2B-Us). Using atomic force microscopy, we characterized the single molecule force-extension curves of the PEVK and N2B-Us spring elements, which together are responsible for physiological levels of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
135
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(152 citation statements)
references
References 41 publications
15
135
2
Order By: Relevance
“…The midpoint force in PullT7 (Fig. 3D) now shifts from 3.5 to 13 pN, showing that the α-actinin/T7 bond can, indeed, resist forces considered physiologically relevant (27)(28)(29). The higher forces for this pulling direction are a consequence of the shorter difference in extension between the bound and the unbound conformations (4 nm of contour length, vs. 34 nm for the PullA-T7 construct, including unfolding of EF3-4): At equilibrium, interaction free energies can be related to the force multiplied by the elongation and the much shorter elongation in the PullT7 construct leads to a higher midpoint unbinding force.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The midpoint force in PullT7 (Fig. 3D) now shifts from 3.5 to 13 pN, showing that the α-actinin/T7 bond can, indeed, resist forces considered physiologically relevant (27)(28)(29). The higher forces for this pulling direction are a consequence of the shorter difference in extension between the bound and the unbound conformations (4 nm of contour length, vs. 34 nm for the PullA-T7 construct, including unfolding of EF3-4): At equilibrium, interaction free energies can be related to the force multiplied by the elongation and the much shorter elongation in the PullT7 construct leads to a higher midpoint unbinding force.…”
Section: Discussionmentioning
confidence: 99%
“…1G). Nonetheless, the midpoint force we measure for the PullA-T7 construct (3.5 pN) is within the physiological range of forces acting on a single titin molecule, estimated to be 0-5 pN in a number of studies (27)(28)(29). The low measured forces in the PullA-T7 construct can be ascribed to the fact that EF3-4 readily unfolds after unbinding of T7, whereas this will not happen if titin and α-actinin are not tethered, as is the case in muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The unique cardiacspecific N2B and PEVK regions are 572 and 186 amino acids long, respectively. The mechanical properties of these regions were recently examined by single molecule AFM techniques and were found to behave like extensible random coils (7)(8)(9). In contrast to mechanically stable folded proteins like the immunoglobulin domains of titin (20), an unstructured protein domain generates a recoiling force that changes monotonically with its length (8).…”
Section: Discussionmentioning
confidence: 99%
“…Those studies of intact titin and the Ig/Fn3 domains have provided a deeper understanding of how the elasticity of titin is adjusted by the sequential unfolding of Ig/Fn3 domains and how its elasticity recovers after domain refolding (Kellermayer et al, 1997;Rief et al, 1997;Carrion-Vazquez et al, 2000). More recently, the mechanical properties of expressed PEVK fragments based on cardiac and soleus PEVK exons were reported Linke et al, 2002;Watanabe et al, 2002;Labeit et al, 2003;Sarkar et al, 2005). Each study observed an unexpectedly broad distribution in the measured elastic persistence length of the PEVK segment.…”
Section: Introductionmentioning
confidence: 99%